Struktur pasar pisang ”kepok” - Jessica Yuliana Bunga; Tomycho Olviana; Doppy Roy Nendissa (University of Islam Malang, 2020)
Bananas are planted almost evenly throughout the territory of Indonesia, including in East Nusa Tenggara (NTT). One of the potential areas of NTT that produces a lot of Kepok bananas is Sikka Regency, especially Paga District. Market structure is one indicator to analysis the level of competition and marketing efficiency. This study aims to analyze the structure of the Kepok market in Paga District, Sikka Regency, involving 45 respondents of banana farmers and ten intermediate traders (between islands). Analysis of the banana market structure uses CR4, HHI, and GR to find the level of market concentration, the barrier to entry, market information, and product differentiation. The results found that in selling banana, banana farmers are at a low concentration level dealing with traders with high concentration levels. Judging from the entry barriers, undifferentiated market, and product information shows that the Kepok banana market is classified as an oligopsonistic imperfect market. In this condition, the farmer is only a price taker, while the price is determined by the trader (price maker). Consequently, the dependence of Kepok banana farmers on intermediary traders is very high, so the hopes of farmers to get a reasonable income have not been achieved. Farmers and trader’s marketing institutions need to regulate market mechanisms to be more efficient. There is a fair distribution among marketing institutions.